A nitrile rubber composition and its application in screw pump stator rubber material

By using nitrile rubber and aromatic hydrocarbon polymer in screw pump stator rubber, combining multifunctional composites and modified calcium carbonate, the damage problem of stator rubber in high temperature and corrosive media environment is solved, achieving higher wear and heat resistance and extending service life.

CN119241930BActive Publication Date: 2025-04-11SHANDONG SHOUGUANG KUNLONG PETROLEUM MACHINERY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411773697.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-04-11
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The existing screw pump stator rubber is prone to damage in high temperature and corrosive media environments, and has high friction, insufficient wear and heat resistance, which affects service life.

Method used

Nitrile rubber is used as the rubber matrix, aromatic hydrocarbon polymer is added to reduce friction, and wear and heat resistance is improved by multifunctional composites and modified calcium carbonate.

Benefits of technology

It effectively reduces friction, improves wear and heat resistance, and extends the service life of stator rubber.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a nitrile rubber composition and application thereof in a screw pump stator rubber material, belonging to the technical field of nitrile rubber compositions; the nitrile rubber composition comprises nitrile rubber, carbon black, a multifunctional composite, modified calcium carbonate, dioctyl phthalate, stearic acid, paraffin, zinc oxide, a promoter NS, an antioxidant RD and sulfur; a preparation method of the modified calcium carbonate comprises the following steps: placing the calcium carbonate in anhydrous ethanol, adding Tween 80 and di(acetylacetonato) diisopropyl titanate for ball milling, raising the temperature to 40-45 DEG C after the ball milling, keeping the temperature for reaction for 1.8-2.2h, filtering, washing and drying after the reaction, so as to obtain the modified calcium carbonate; the nitrile rubber composition provided by the invention is used for a stator rubber material, has strong toughness, high mechanical property, low friction, good wear resistance and good hot oil resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nitrile rubber compositions, and in particular relates to a nitrile rubber composition and application thereof in a screw pump stator rubber material. Background Art

[0002] Screw pumps are usually used in crude oil extraction technology. They have high working efficiency and are mostly used in booster stations and transfer stations. They are gradually being widely used in coal mining, petroleum, hydraulic power and other fields.

[0003] The main working parts of the screw pump are composed of a rotor and a stator. The rotor refers to the screw of the eccentric spiral body, which rotates spirally around the central axis during operation. The stator is composed of a steel jacket and a rubber bushing. The stator rubber bushing is a cavity device that is cast and bonded to the steel jacket with a rubber material and has a double-line spiral surface on the inner surface. The screw pump inhales and discharges liquid through the volume change of the sealed cavity formed by the rotor and the stator.

[0004] The performance of the stator rubber directly affects the service life of the screw pump. However, the existing screw pump stator rubber has the following problems during use:

[0005] First, a lot of heat will be generated during the operation of the screw pump, so that the stator rubber will always maintain a high temperature. At high temperatures, the internal molecular chain of the rubber is highly active and unstable. The rotor will impact the stator rubber during movement, causing mechanical damage. Since the surface of the existing screw pump stator rubber on the market is matte, the friction heat generation is more intense when the stator rubber is not fully lubricated. In addition, there will be sand particles in the process of crude oil extraction, which will cause long-term wear on the stator rubber, thus affecting the performance of the stator rubber.

[0006] Second, crude oil usually contains corrosive media such as hydrogen sulfide and carbon dioxide, which can harden the stator rubber under the action of heat, reduce the strength of the stator rubber, and shorten the service life of the stator;

[0007] Third, when the gas-liquid ratio in the oil well is relatively high, the gas will cause gas infiltration and swelling of the stator rubber. During the rotation of the stator, the stator and rotor will interfere with each other, increasing the friction between the rotor and the stator. Excessive swelling will cause difficulties in rotor rotation, locking, and breakage. Gas infiltration and swelling will not only increase the friction between the stator and the rotor, but also the large amount of heat generated by friction is not easily carried away by the fluid with a high gas content. In addition, the stator cannot be fully lubricated, making the stator vulnerable to damage.

[0008] Therefore, improving the lubricity of the stator rubber, reducing the friction between the screw pump and the rotor during operation, and improving the wear resistance, oil resistance and heat resistance of the stator rubber are the research directions of technicians.

[0009] Nitrile rubber is a carbon chain unsaturated polar rubber made from butadiene and acrylonitrile by emulsion polymerization. It has the advantages of good oil resistance, high wear resistance, good heat resistance and strong adhesion, and low cost. Nitrile rubber has become the main type of stator rubber on the market. However, the temperature resistance of nitrile rubber is limited. It can only maintain good performance at lower temperatures, and its wear performance cannot meet higher usage requirements.

[0010] CN117903511A discloses a hydrogenated nitrile rubber composition, a vulcanized rubber, and a preparation method and application thereof, and specifically discloses that the hydrogenated nitrile rubber composition contains nitrile rubber, carbon black, white carbon black, a silane coupling agent, an activator, a plasticizer, an antioxidant, and a peroxide vulcanizing agent; under the coordinated cooperation of the components, the vulcanized rubber has higher mechanical strength and wear resistance, and reduces the dynamic heat generation of the vulcanized rubber;

[0011] This patent mainly reduces the dynamic heat generation of vulcanized rubber and improves the wear resistance of the rubber composition by synergizing silica, carbon black and rubber matrix. However, the silica in this patent has poor compatibility with the rubber matrix and poor dispersion in the rubber matrix, which affects the homogeneity and stability of the rubber material and ultimately affects the mechanical properties of the product. In addition, the rubber material obtained has poor resistance to hot oil.

[0012] During the research and development process, the applicant discovered that adding aromatic hydrocarbon polymers during the preparation process can effectively make the stator rubber surface present a mirror state and effectively reduce friction. However, aromatic hydrocarbon polymers usually contain benzene ring structures, which make the aromatic hydrocarbon polymer surface rigid, while nitrile rubber exhibits flexibility. The interface bonding between nitrile rubber and aromatic hydrocarbon polymers is poor, which affects the uniformity and consistency of the nitrile rubber composition, and further reduces the mechanical properties of the nitrile rubber composition; and when adding aromatic hydrocarbon polymers, a small amount added cannot play a good lubricating role, and a large amount added will make the rubber brittle, making the product easier to break and weakening the heat resistance, ultimately affecting the comprehensive performance of the stator rubber and shortening the service life of the screw pump.

[0013] In the prior art, the applicant has not found any relevant research on adding aromatic hydrocarbon polymers to a nitrile rubber composition to make the stator rubber present a mirror effect and reduce friction; therefore, it is necessary to provide a nitrile rubber composition and its application in a screw pump stator rubber material, by adding aromatic hydrocarbon polymers to make the stator rubber present a mirror effect, effectively reduce friction, enhance wear resistance, and extend the service life of the screw pump stator rubber. Summary of the invention

[0014] In order to solve the technical problems existing in the prior art, the present invention provides a nitrile rubber composition and its application in the stator rubber material of a screw pump. By adding an aromatic hydrocarbon polymer, the stator rubber presents a mirror effect, which can effectively reduce friction, improve wear resistance, ensure heat resistance, enhance oil resistance, and improve mechanical properties such as fracture resistance.

[0015] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0016] A nitrile rubber composition, comprising, by weight, 98-103 parts of nitrile rubber, 54-56 parts of carbon black, 9.0-9.5 parts of a multifunctional compound, 9.0-12.0 parts of modified calcium carbonate, 9.7-10.3 parts of dioctyl phthalate, 1.8-2.2 parts of stearic acid, 0.9-1.1 parts of paraffin, 4.8-5.3 parts of zinc oxide, 1.3-1.6 parts of an accelerator NS, 0.8-1.1 parts of an antioxidant RD, and 1.4-1.7 parts of sulfur;

[0017] The preparation method of the modified calcium carbonate comprises the following steps: placing calcium carbonate in anhydrous ethanol, adding Tween 80 and di(acetylacetonato)titanate diisopropyl for ball milling, wherein the ball milling temperature is 27-33 min, the ball milling speed is 224-235 rpm, and the ball-to-material ratio is 3-5:1. After the ball milling is completed, the temperature is increased to 40-45° C., and the temperature is kept for reaction for 1.8-2.2 hours. After the reaction is completed, the modified calcium carbonate is filtered, washed, and dried to obtain the modified calcium carbonate.

[0018] The particle size of the calcium carbonate is 200-220 nm;

[0019] The mass ratio of the calcium carbonate, anhydrous ethanol, Tween 80 and di(acetylacetonato) diisopropyl titanate is 10.6-11.0:98-104:0.8-1.2:1.1-1.3.

[0020] The method for preparing the multifunctional composite comprises the following steps:

[0021] 1. Hexagonal Boron Nitride Pretreatment

[0022] Spraying the pretreatment liquid into the hexagonal boron nitride, controlling the spraying rate to be 4.7-5.2 g / min, raising the temperature to 68-72° C. after the spraying, and keeping the temperature to react for 5.8-6.2 hours, cooling, filtering, washing, and drying after the reaction, to obtain the pretreated hexagonal boron nitride;

[0023] The particle size of the hexagonal boron nitride is 150-180nm;

[0024] The mass ratio of hexagonal boron nitride to pretreatment liquid is 9.8-10.2:98-105;

[0025] The pretreatment solution is a mixture of ethanol solution, vinylethoxydimethylsilane and polyvinylpyrrolidone, and the mass ratio of the ethanol solution, vinylethoxydimethylsilane and polyvinylpyrrolidone is 72-77:1.1-1.3:0.8-1.2;

[0026] The mass concentration of the ethanol solution is 40-44%;

[0027] 2. One-time compound

[0028] The pretreated hexagonal boron nitride is placed in an ethanol solution and dispersed evenly to obtain a pretreated hexagonal boron nitride mixed solution; benzoyl peroxide is added to styrene and dispersed evenly to obtain a monomer mixed solution; the monomer mixed solution is added dropwise to the pretreated hexagonal boron nitride mixed solution, and the addition rate is controlled to be 2.6-3.4mL / min. After the addition is completed, polyvinyl alcohol is added, and after stirring evenly, the oil bath is heated, and the heating rate is controlled to be 1.6-2.2℃ / min, and the temperature is increased to 71-75℃, and the temperature is kept for reaction for 1.8-2.2h. After the reaction is completed, the temperature is increased to 78-82℃ at a rate of 0.4-0.6℃ / min, and the temperature is kept for reaction for 6.0-8.0h. After the reaction is completed, it is cooled and washed, and then dried at 58-62℃ for 11.0-13.0h to obtain a primary composite microsphere;

[0029] The mass concentration of the ethanol solution is 78-82%;

[0030] The mass ratio of the pretreated hexagonal boron nitride to the ethanol solution is 7.8-8.2:48-52;

[0031] The mass ratio of the benzoyl peroxide to styrene is 0.11-0.13:18-23;

[0032] The mass ratio of the pretreated hexagonal boron nitride mixed solution, the monomer mixed solution and the polyvinyl alcohol is 12.2-12.5:9.8-10.2:0.37-0.43.

[0033] 3. Surface treatment

[0034] The primary composite microspheres are placed in a sulfuric acid solution, mixed evenly, and then the temperature is controlled to be 38-42°C, and the mixture is stirred for 3.7-4.2 hours. Then, an ethanol solution is added, and the mixture is naturally cooled to room temperature. After washing and drying, the sulfonated primary composite microspheres are obtained.

[0035] The mass concentration of the sulfuric acid solution is 93-98%;

[0036] The volume concentration of the ethanol solution is 46-53%;

[0037] The mass ratio of the primary composite microspheres, the sulfuric acid solution and the ethanol solution is 1.6-1.8 g: 47-53 mL: 38-43 mL.

[0038] 4. Secondary compound

[0039] Add the sulfonated primary composite microspheres to deionized water, then add octadecyltrimethylammonium chloride and didodecyldimethylammonium bromide, stir evenly, add modified graphene, stir at 495-510rpm for 1.4-1.6h, filter and wash after completion of stirring, and then freeze-dry at a drying temperature of -34 to -30°C for 9.7-10.2h, and wait until it naturally returns to room temperature to obtain a multifunctional composite;

[0040] The volume mass ratio of the deionized water, the sulfonated primary composite microspheres, octadecyltrimethylammonium chloride, didodecyldimethylammonium bromide, and the modified graphene is 290-310 mL: 8.6-8.8 g: 0.6-0.8 g: 0.3-0.6 g: 2.0-2.5 g;

[0041] The preparation method of the modified graphene comprises placing the graphene in a hydrogen peroxide solution and a nitric acid solution, raising the temperature to 70-74° C., stirring and reacting for 5.8-6.2 hours, cooling and washing after the stirring reaction is completed to obtain hydroxylated graphene; placing the hydroxylated graphene in N,N-dimethylformamide, adding sodium dodecylbenzenesulfonate, performing ultrasonic dispersion treatment, then adding oleic acid, stirring evenly, then adding dicyclohexylcarbodiimide and 4-dimethylaminopyridine, raising the temperature to 74-77° C., stirring and reacting for 9.8-10.4 hours, filtering, washing and drying after the reaction is completed to obtain the modified graphene;

[0042] The particle size of the graphene is 270-290nm;

[0043] The mass volume ratio of the graphene, hydrogen peroxide solution and nitric acid solution is 13.1-13.7 g:95-105 mL:98-102 mL;

[0044] The mass concentration of the hydrogen peroxide solution is 32-35%, and the mass concentration of the nitric acid solution is 62-67%;

[0045] The mass volume ratio of the hydroxylated graphene, N,N-dimethylformamide, sodium dodecylbenzenesulfonate, oleic acid, dicyclohexylcarbodiimide and 4-dimethylaminopyridine is 3.0-3.5 g: 295-305 mL: 1.1-1.4 g: 4.0-4.2 g: 7.3-7.8 g: 0.32-0.36 g.

[0046] Application of a nitrile rubber composition in the stator rubber of a screw pump.

[0047] Compared with the prior art, the present invention has achieved the following beneficial effects:

[0048] 1. The present invention adopts nitrile rubber as a rubber matrix to prepare a rubber composition, wherein a specific multifunctional compound and a modified calcium carbonate component are added, wherein the modified calcium carbonate is calcium carbonate treated with a titanate coupling agent, thereby improving the dispersibility of calcium carbonate in the rubber matrix and the compatibility of the rubber matrix, and avoiding the agglomeration of calcium carbonate particles; in the preparation of the multifunctional compound, hexagonal boron nitride is first introduced, which has good thermal conductivity and toughness, and vinyl groups are introduced on its surface after pretreatment, thereby improving its lipophilicity, and in a compounding step, styrene is better polymerized on its surface, Polystyrene can be evenly and completely coated on the surface of hexagonal boron nitride, improving the compatibility between the two. As an aromatic hydrocarbon polymer, polystyrene has good smoothness and fluidity, good gloss, and is helpful to achieve a better blending system and improve the structural uniformity of the nitrile rubber composition. Then, the surface of the primary composite microspheres is sulfonated with concentrated sulfuric acid, so that the surface of the primary composite microspheres contains more negative charges. In the secondary composite step, the microspheres are combined with a cationic surfactant, and modified graphene is introduced on the surface of the microspheres. The modified graphene is prepared by esterification reaction of the hydroxyl groups on the surface of the microspheres with oleic acid. The surface contains more negative charges such as hydroxyl and carboxyl groups, and can also be well combined with cationic surfactants. Graphene has excellent strength and thermal conductivity, which improves the strength and thermal conductivity of the nitrile rubber composition, achieves the purpose of stable combination of hexagonal boron nitride, polystyrene and graphene, and solves the problem of poor compatibility between rigid polystyrene and flexible nitrile rubber. It has good dispersibility in the rubber matrix, which improves the homogeneity and stability of the nitrile rubber composition; the multifunctional composite, modified calcium carbonate and other ingredients are compounded to prepare the nitrile rubber composition, which is applied to screw stator rubber, The dispersion of polystyrene in the rubber matrix is ​​improved, and the advantages of good smoothness and high gloss of polystyrene are fully utilized, so that the nitrile rubber composition presents a mirror effect and reduces friction. In addition, both graphene and hexagonal boron nitride have good thermal conductivity. During the use of the screw stator rubber, the heat generated by friction can be quickly conducted out, thereby improving the wear resistance of the stator rubber. In combination with other ingredients such as modified calcium carbonate, the toughness and strength of the stator rubber are effectively improved, and the stability of the stator rubber during use is good, and the heat resistance and oil resistance of the stator rubber are improved.

[0049] 2. The nitrile rubber composition of the present invention is used for the rubber material of the screw stator, and the Shore A hardness is measured to be 75-78, the tensile strength is 26.3-27.4 MPa, the elongation at break is 516-525%, the tear strength is 63.2-64.3 MPa, the 300% tensile strength is 20.6-21.2 MPa, and the Akron abrasion is 0.085-0.095;

[0050] 3. The nitrile rubber composition of the present invention is used for the screw stator rubber material, and is immersed in 5 times the mass of 100°C, 0# diesel for 168 hours. After the immersion, the Shore A hardness of the rubber material is measured again, which is 71-75, the tensile strength is 25.2-26.5 MPa, the elongation at break is 487-499%, the tear strength is 60.0-61.5 MPa, the 300% tensile strength is 19.9-21.7 MPa, the Akron abrasion is 0.098-0.117, and the volume change rate is 1.7-2.1%. DETAILED DESCRIPTION

[0051] In order to more clearly understand the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.

[0052] Example 1

[0053] A nitrile rubber composition, comprising 100 parts of nitrile rubber, 55 parts of carbon black, 9.3 parts of a multifunctional compound, 10.0 parts of modified calcium carbonate, 10.0 parts of dioctyl phthalate, 2.0 parts of stearic acid, 1.0 part of paraffin, 5.0 parts of zinc oxide, 1.5 parts of an accelerator NS, 1.0 parts of an antioxidant RD, and 1.5 parts of sulfur;

[0054] The preparation method of the modified calcium carbonate is as follows: 10.8g of calcium carbonate is placed in 100g of anhydrous ethanol, 1.0g of Tween 80 and 1.2g of di(acetylacetonato)titanate diisopropyl are added for ball milling, the ball milling temperature is 30min, the ball milling speed is 230rpm, the ball-to-material ratio is 4:1, after the ball milling is completed, the temperature is increased to 42°C, the temperature is kept for reaction for 2.0h, after the reaction is completed, filtering, washing and drying are performed to obtain the modified calcium carbonate;

[0055] The particle size of the calcium carbonate is 210 nm.

[0056] The method for preparing the multifunctional composite comprises the following steps:

[0057] 1. Hexagonal Boron Nitride Pretreatment

[0058] 100 g of the pretreatment solution was sprayed into 10.0 g of hexagonal boron nitride, and the spraying rate was controlled to be 5.0 g / min. After the spraying was completed, the temperature was raised to 70° C. and the reaction was kept warm for 6.0 hours. After the reaction was completed, the pretreatment was obtained by cooling, filtering, washing, and drying.

[0059] The particle size of the hexagonal boron nitride is 160nm;

[0060] The pretreatment solution is a mixture of ethanol solution, vinylethoxydimethylsilane and polyvinylpyrrolidone, and the mass ratio of the ethanol solution, vinylethoxydimethylsilane and polyvinylpyrrolidone is 75:1.2:1.0;

[0061] The mass concentration of the ethanol solution is 42%;

[0062] 2. One-time compound

[0063] 8.0g of pretreated hexagonal boron nitride was placed in 50g of ethanol solution and dispersed evenly to obtain a pretreated hexagonal boron nitride mixed solution; 0.12g of benzoyl peroxide was added to 20g of styrene and dispersed evenly to obtain a monomer mixed solution; 10.0g of the monomer mixed solution was added dropwise to 12.4g of the pretreated hexagonal boron nitride mixed solution, and the addition rate was controlled to be 3.0mL / min. After the addition was completed, 0.40g of polyvinyl alcohol was added, and the mixture was stirred evenly and heated in an oil bath. The heating rate was controlled to be 2.0℃ / min, and the temperature was raised to 73℃, and the reaction was kept warm for 2.0h. After the reaction was completed, the temperature was raised to 80℃ at a rate of 0.5℃ / min, and the reaction was kept warm for 7.0h. After the reaction was completed, it was cooled and washed, and then dried at 60℃ for 12.0h to obtain a primary composite microsphere;

[0064] The mass concentration of the ethanol solution is 80%;

[0065] 3. Surface treatment

[0066] 1.7 g of primary composite microspheres were placed in 50 mL of 95 wt% sulfuric acid solution, mixed evenly, and then the temperature was controlled at 40°C, and the mixture was stirred for 4.0 h. Then 40 mL of ethanol solution was added, and the mixture was naturally cooled to room temperature. After washing and drying, sulfonated primary composite microspheres were obtained.

[0067] The volume concentration of the ethanol solution is 50%;

[0068] 4. Secondary compound

[0069] 8.7 g of sulfonated primary composite microspheres were added to 300 mL of deionized water, and then 0.7 g of octadecyltrimethylammonium chloride and 0.5 g of didodecyldimethylammonium bromide were added. After stirring evenly, 2.1 g of modified graphene was added and stirred at 500 rpm for 1.5 h. After the stirring was completed, the mixture was filtered and washed and then freeze-dried at a drying temperature of -32 ° C for 10.0 h. After the mixture was naturally restored to room temperature, a multifunctional composite was obtained.

[0070] The preparation method of the modified graphene is as follows: 13.4g of graphene is placed in 100mL of hydrogen peroxide solution and 100mL of nitric acid solution, the temperature is increased to 72°C, the stirring reaction is performed for 6.0h, after the stirring reaction is completed, the temperature is lowered, and the mixture is washed to obtain hydroxylated graphene; 3.3g of hydroxylated graphene is placed in 300mL of N,N-dimethylformamide, 1.3g of sodium dodecylbenzene sulfonate is added, ultrasonic dispersion treatment is performed, 4.1g of oleic acid is added, the mixture is stirred evenly, 7.5g of dicyclohexylcarbodiimide and 0.34g of 4-dimethylaminopyridine are added, the temperature is increased to 76°C, the stirring reaction is performed for 10.0h, after the reaction is completed, the mixture is filtered, washed, and dried to obtain the modified graphene;

[0071] The particle size of the graphene is 280nm;

[0072] The mass concentration of the hydrogen peroxide solution is 33%, and the mass concentration of the nitric acid solution is 65%.

[0073] Example 2

[0074] A nitrile rubber composition, comprising 98 parts of nitrile rubber, 54 parts of carbon black, 9.0 parts of a multifunctional compound, 9.0 parts of modified calcium carbonate, 9.7 parts of dioctyl phthalate, 1.8 parts of stearic acid, 0.9 parts of paraffin, 4.8 parts of zinc oxide, 1.3 parts of an accelerator NS, 0.8 parts of an antioxidant RD, and 1.4 parts of sulfur;

[0075] The preparation method of the modified calcium carbonate is as follows: 10.6 g of calcium carbonate is placed in 98 g of anhydrous ethanol, 0.8 g of Tween 80 and 1.1 g of di(acetylacetonato)titanate diisopropyl are added for ball milling, the ball milling temperature is 27 min, the ball milling speed is 224 rpm, the ball-to-material ratio is 3:1, after the ball milling is completed, the temperature is increased to 40° C., the temperature is kept for reaction for 1.8 hours, and after the reaction is completed, the modified calcium carbonate is filtered, washed, and dried to obtain the modified calcium carbonate;

[0076] The particle size of the calcium carbonate is 200 nm.

[0077] The method for preparing the multifunctional composite comprises the following steps:

[0078] 1. Hexagonal Boron Nitride Pretreatment

[0079] 98 g of the pretreatment solution was sprayed into 9.8 g of hexagonal boron nitride at a spray rate of 4.7 g / min. After the spraying was completed, the temperature was raised to 68° C. and the reaction was kept warm for 5.8 hours. After the reaction was completed, the pretreatment hexagonal boron nitride was obtained by cooling, filtering, washing and drying.

[0080] The particle size of the hexagonal boron nitride is 150nm;

[0081] The pretreatment solution is a mixture of ethanol solution, vinylethoxydimethylsilane and polyvinylpyrrolidone, and the mass ratio of the ethanol solution, vinylethoxydimethylsilane and polyvinylpyrrolidone is 72:1.1:0.8;

[0082] The mass concentration of the ethanol solution is 40%;

[0083] 2. One-time compound

[0084] 7.8g of pretreated hexagonal boron nitride was placed in 48g of ethanol solution and dispersed evenly to obtain a pretreated hexagonal boron nitride mixed solution; 0.11g of benzoyl peroxide was added to 18g of styrene and dispersed evenly to obtain a monomer mixed solution; 9.8g of the monomer mixed solution was added dropwise to 12.2g of the pretreated hexagonal boron nitride mixed solution, and the addition rate was controlled to be 2.6mL / min. After the addition was completed, 0.37g of polyvinyl alcohol was added, and the mixture was stirred evenly and heated in an oil bath. The heating rate was controlled to be 1.6℃ / min, and the temperature was raised to 71℃. The mixture was kept warm for 1.8h. After the reaction was completed, the mixture was heated to 78℃ at a rate of 0.4℃ / min and kept warm for 6.0h. After the reaction was completed, the mixture was cooled and washed, and then dried at 58℃ for 13.0h to obtain a primary composite microsphere;

[0085] The mass concentration of the ethanol solution is 78%;

[0086] 3. Surface treatment

[0087] 1.6 g of primary composite microspheres were placed in 47 mL of 93 wt% sulfuric acid solution, mixed evenly, and then the temperature was controlled at 38 °C, and the mixture was stirred for 3.7 h. Then 38 mL of ethanol solution was added, and the mixture was naturally cooled to room temperature. After washing and drying, sulfonated primary composite microspheres were obtained.

[0088] The volume concentration of the ethanol solution is 46%;

[0089] 4. Secondary compound

[0090] 8.6 g of sulfonated primary composite microspheres were added to 290 mL of deionized water, and then 0.6 g of octadecyltrimethylammonium chloride and 0.3 g of didodecyldimethylammonium bromide were added. After stirring evenly, 2.0 g of modified graphene was added and stirred at 495 rpm for 1.4 h. After the stirring was completed, the mixture was filtered and washed and then freeze-dried at a drying temperature of -34 ° C for 9.7 h. The mixture was allowed to naturally return to room temperature to obtain a multifunctional composite.

[0091] The preparation method of the modified graphene is as follows: 13.1g of graphene is placed in 95mL of hydrogen peroxide solution and 98mL of nitric acid solution, the temperature is increased to 70°C, the reaction is stirred for 5.8h, after the reaction is completed, the temperature is lowered, and the mixture is washed to obtain hydroxylated graphene; 3.0g of hydroxylated graphene is placed in 295mL of N,N-dimethylformamide, 1.1g of sodium dodecylbenzene sulfonate is added, ultrasonic dispersion treatment is performed, 4.0g of oleic acid is added, the mixture is stirred evenly, 7.3g of dicyclohexylcarbodiimide and 0.32g of 4-dimethylaminopyridine are added, the temperature is increased to 74°C, the reaction is stirred for 9.8h, after the reaction is completed, the mixture is filtered, washed, and dried to obtain the modified graphene;

[0092] The particle size of the graphene is 270nm;

[0093] The mass concentration of the hydrogen peroxide solution is 32%, and the mass concentration of the nitric acid solution is 62%.

[0094] Example 3

[0095] A nitrile rubber composition, comprising 103 parts of nitrile rubber, 56 parts of carbon black, 9.5 parts of a multifunctional compound, 12.0 parts of modified calcium carbonate, 10.3 parts of dioctyl phthalate, 2.2 parts of stearic acid, 1.1 parts of paraffin, 5.3 parts of zinc oxide, 1.6 parts of an accelerator NS, 1.1 parts of an antioxidant RD, and 1.7 parts of sulfur;

[0096] The preparation method of the modified calcium carbonate is as follows: 11.0g of calcium carbonate is placed in 104g of anhydrous ethanol, 1.2g of Tween 80 and 1.3g of di(acetylacetonato)titanate diisopropyl are added for ball milling, the ball milling temperature is 33min, the ball milling speed is 235rpm, the ball-to-material ratio is 5:1, after the ball milling is completed, the temperature is increased to 45°C, the temperature is kept for reaction for 2.2h, after the reaction is completed, the modified calcium carbonate is filtered, washed and dried to obtain the modified calcium carbonate;

[0097] The particle size of the calcium carbonate is 220 nm.

[0098] The method for preparing the multifunctional composite comprises the following steps:

[0099] 1. Hexagonal Boron Nitride Pretreatment

[0100] 105 g of the pretreatment solution was sprayed into 10.2 g of hexagonal boron nitride at a spray rate of 5.2 g / min. After the spraying was completed, the temperature was raised to 72°C and the reaction was kept warm for 6.2 hours. After the reaction was completed, the pretreatment hexagonal boron nitride was obtained by cooling, filtering, washing and drying.

[0101] The particle size of the hexagonal boron nitride is 180 nm;

[0102] The pretreatment solution is a mixture of ethanol solution, vinylethoxydimethylsilane and polyvinylpyrrolidone, and the mass ratio of the ethanol solution, vinylethoxydimethylsilane and polyvinylpyrrolidone is 77:1.3:1.2;

[0103] The mass concentration of the ethanol solution is 44%;

[0104] 2. One-time compound

[0105] 8.2g of pretreated hexagonal boron nitride was placed in 52g of ethanol solution and dispersed evenly to obtain a pretreated hexagonal boron nitride mixed solution; 0.13g of benzoyl peroxide was added to 23g of styrene and dispersed evenly to obtain a monomer mixed solution; 10.2g of the monomer mixed solution was added dropwise to 12.5g of the pretreated hexagonal boron nitride mixed solution, and the addition rate was controlled to be 3.4mL / min. After the addition was completed, 0.43g of polyvinyl alcohol was added, and the mixture was stirred evenly and heated in an oil bath. The heating rate was controlled to be 2.2℃ / min, and the temperature was raised to 75℃, and the reaction was kept warm for 2.2h. After the reaction was completed, the temperature was raised to 82℃ at a rate of 0.6℃ / min, and the reaction was kept warm for 8.0h. After the reaction was completed, it was cooled and washed, and then dried at 62℃ for 11.0h to obtain a primary composite microsphere;

[0106] The mass concentration of the ethanol solution is 82%;

[0107] 3. Surface treatment

[0108] 1.8 g of primary composite microspheres were placed in 53 mL of 98 wt% sulfuric acid solution, mixed evenly, and then the temperature was controlled to 42°C, and the mixture was stirred for 4.2 h. Then 43 mL of ethanol solution was added, and the mixture was naturally cooled to room temperature. After washing and drying, sulfonated primary composite microspheres were obtained.

[0109] The volume concentration of the ethanol solution is 53%;

[0110] 4. Secondary compound

[0111] 8.8 g of sulfonated primary composite microspheres were added to 310 mL of deionized water, and then 0.8 g of octadecyltrimethylammonium chloride and 0.6 g of didodecyldimethylammonium bromide were added. After stirring evenly, 2.2 g of modified graphene was added and stirred at 510 rpm for 1.6 h. After the stirring was completed, the mixture was filtered and washed and then freeze-dried at a drying temperature of -30 ° C for 10.2 h. The mixture was allowed to naturally return to room temperature to obtain a multifunctional composite.

[0112] The modified graphene preparation method comprises the following steps: placing 13.7 g of graphene in 105 mL of hydrogen peroxide solution and 102 mL of nitric acid solution, raising the temperature to 74° C., stirring and reacting for 6.2 h, cooling and washing after the stirring and reaction are completed to obtain hydroxylated graphene; placing 3.5 g of hydroxylated graphene in 305 mL of N,N-dimethylformamide, adding 1.4 g of sodium dodecylbenzene sulfonate, performing ultrasonic dispersion treatment, then adding 4.2 g of oleic acid, stirring evenly, then adding 7.8 g of dicyclohexylcarbodiimide and 0.36 g of 4-dimethylaminopyridine, raising the temperature to 77° C., stirring and reacting for 10.4 h, filtering, washing and drying after the reaction is completed to obtain the modified graphene;

[0113] The particle size of the graphene is 290nm;

[0114] The mass concentration of the hydrogen peroxide solution is 35%, and the mass concentration of the nitric acid solution is 67%.

[0115] Comparative Example 1

[0116] Based on Example 1, the changes are as follows:

[0117] In the method for preparing the multifunctional composite,

[0118] (1) The surface treatment step is omitted and in the secondary composite step, an equal amount of sulfonated primary composite microspheres is replaced by primary composite microspheres;

[0119] (2) In the secondary composite step, the preparation method of modified graphene is omitted; the modified graphene is replaced with untreated graphene in equal amounts, and the primary composite microspheres and the untreated graphene are mixed evenly;

[0120] The secondary composite step is to add 8.7g of primary composite microspheres to 300mL of deionized water, stir evenly, add 2.1g of graphene, stir at 500rpm for 1.5h, filter and wash, and then freeze-dry at -32°C for 10.0h, and wait until it naturally returns to room temperature to obtain a multifunctional composite;

[0121] The particle size of the graphene is 280nm;

[0122] The rest of the operations are the same.

[0123] Comparative Example 2

[0124] Based on Example 1, the changes are as follows:

[0125] The hexagonal boron nitride pretreatment step is omitted, and in a compounding step, the pretreated hexagonal boron nitride is replaced by an equal amount of untreated boron nitride;

[0126] The primary mixing step comprises placing 8.0 g of hexagonal boron nitride in 50 g of ethanol solution and dispersing the mixture uniformly to obtain a hexagonal boron nitride mixed solution; dropping 10.0 g of polystyrene and 0.40 g of polyvinyl alcohol into 12.4 g of the mixed solution, stirring the mixture uniformly, heating the mixture in an oil bath, controlling the heating rate to be 2.0° C. / min, raising the temperature to 73° C., and keeping the temperature for reaction for 2.0 h. After the reaction is completed, heating the mixture to 80° C. at a rate of 0.5° C. / min, and keeping the temperature for reaction for 7.0 h. After the reaction is completed, cooling and washing the mixture, and drying the mixture at 60° C. for 12.0 h to obtain a primary composite microsphere;

[0127] The rest of the operations are the same.

[0128] Application Examples

[0129] The preparation method of the nitrile rubber composition comprises the following steps: placing the nitrile rubber in an open mill for plasticizing for 20 minutes, then adding carbon black, a multifunctional compound, modified calcium carbonate, dioctyl phthalate, stearic acid, paraffin, zinc oxide, an accelerator NS, an antioxidant RD, and sulfur, adjusting the roller distance to 0.6 mm, performing triangular packing 8 times, adjusting the roller distance to 1.0 mm, unrolling the sheet, and cooling the sheet in air for 28.0 hours to obtain the nitrile rubber composition;

[0130] The nitrile rubber composition is used in the screw pump stator rubber material. The nitrile rubber composition is placed in a vulcanizer for vulcanization treatment. The vulcanization temperature is 160° C., the pressure is 12.5 MPa, and the vulcanization time is 40 minutes to obtain the screw pump stator rubber material.

[0131] Performance Testing

[0132] According to the formulations of Examples 1-3 and Comparative Examples 1-2, respectively, a nitrile rubber composition was prepared according to the preparation method of the nitrile rubber composition in the application example, and then the nitrile rubber composition was applied to the screw pump stator rubber material according to the method of the application example. The screw pump stator rubber materials obtained were subjected to the following performance tests, and the test results are as follows:

[0133] 1. Basic performance

[0134]

[0135] 2. Hot oil resistance

[0136] The stator rubber materials obtained in Examples 1-3 and Comparative Examples 1-2 were immersed in 5 times the mass of 100°C, 0# diesel for 168 hours. After the immersion, the performance of the rubber materials was tested again. The test results are as follows:

[0137]

[0138] The present invention adopts nitrile rubber as a rubber matrix to prepare a rubber composition, wherein a specific multifunctional composite and a modified calcium carbonate component are added, wherein the modified calcium carbonate is obtained by treating the calcium carbonate with a titanate coupling agent, thereby improving the dispersibility of the calcium carbonate in the rubber matrix and the compatibility with the rubber matrix, and avoiding the agglomeration of the calcium carbonate particles; in the preparation of the multifunctional composite, hexagonal boron nitride is firstly introduced, which has good thermal conductivity and toughness, and vinyl groups are introduced on its surface after pretreatment, thereby improving its lipophilicity; in a first composite step, styrene is better polymerized on its surface, and polystyrene can be uniformly and completely coated on the surface of the hexagonal boron nitride, thereby improving the compatibility between the two; as an aromatic hydrocarbon polymer, polystyrene has good smoothness and fluidity, good glossiness, and is helpful to achieve a better blending system, thereby improving the structural uniformity of the nitrile rubber composition; then, the surface of the first composite microsphere is subjected to a surface sulfonation treatment with concentrated sulfuric acid, thereby causing the surface of the first composite microsphere to contain more negative charges; in a second composite step, the microsphere is combined with a cationic surfactant, and modified graphene is introduced on its surface, wherein the modified graphene is prepared by an esterification reaction between a hydroxyl group on its surface and oleic acid, and its surface It contains more negative charges such as hydroxyl and carboxyl groups, and can also be well combined with cationic surfactants. Graphene has excellent strength and thermal conductivity, which improves the strength and thermal conductivity of the nitrile rubber composition, achieves the purpose of stable combination of hexagonal boron nitride, polystyrene and graphene, and solves the problem of poor compatibility between rigid polystyrene and flexible nitrile rubber. It has good dispersibility in the rubber matrix, and improves the homogeneity and stability of the nitrile rubber composition; the multifunctional composite, modified calcium carbonate and other ingredients are compounded to prepare the nitrile rubber composition, which is applied to the screw stator rubber to improve The dispersion of polystyrene in the rubber matrix is ​​improved, and the advantages of good smoothness and high gloss of polystyrene are fully utilized, so that the nitrile rubber composition presents a mirror effect and reduces friction. In addition, both graphene and hexagonal boron nitride have good thermal conductivity. During the use of the screw stator rubber, the heat generated by friction can be quickly discharged, thereby improving the wear resistance of the stator rubber. Combined with other ingredients such as modified calcium carbonate, the toughness and strength of the stator rubber are effectively improved, and the stability of the stator rubber during use is good, thereby improving the heat resistance and oil resistance of the stator rubber.

[0139] Comparative Example 1 omits the surface treatment step of the primary composite microspheres. In the secondary composite step, the primary composite microspheres are directly mixed with graphene that has not been treated in any way. The miscibility of the primary composite microspheres with the graphene is poor, and the two cannot be dispersed evenly. In addition, the primary composite microspheres are polystyrene-coated hexagonal boron nitride microspheres. The rigid polystyrene and the rubber matrix still have poor compatibility and poor interface bonding, which affects the uniformity and stability of the nitrile rubber composition, causing the components to be unevenly dispersed. When used for stator rubber, the friction is large, the wear resistance is poor, the strength is not high, and the stability is poor.

[0140] In Comparative Example 2, the pretreatment step of hexagonal boron nitride is omitted, and hexagonal boron nitride and polystyrene without any treatment are mixed. The compatibility of hexagonal boron nitride and polystyrene is poor, and the two are not well dispersed, which affects the subsequent surface treatment and secondary composite steps, and cannot give full play to the advantage of good gloss of polystyrene, affecting the toughness of hexagonal boron nitride. The multifunctional composite finally obtained is in a state of agglomeration and uneven dispersion, which affects the binding of modified graphene on its surface, reduces the stability of the multifunctional composite microspheres, weakens the thermal conductivity, and the interface bonding between polystyrene and the rubber matrix is ​​poor. The rubber composition finally obtained has poor smoothness, poor wear resistance, and poor strength and stability.

[0141] Unless otherwise specified, all percentages used in the present invention are by mass.

[0142] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A nitrile rubber composition, characterized in that In parts by weight, it includes 98-103 parts of nitrile rubber, 54-56 parts of carbon black, 9.0-9.5 parts of multifunctional compound, 9.0-12.0 parts of modified calcium carbonate, 9.7-10.3 parts of dioctyl phthalate, 1.8-2.2 parts of stearic acid, 0.9-1.1 parts of paraffin, 4.8-5.3 parts of zinc oxide, 1.3-1.6 parts of accelerator NS, 0.8-1.1 parts of antioxidant RD, and 1.4-1.7 parts of sulfur; The preparation method of the multifunctional composite comprises the steps of hexagonal boron nitride pretreatment, primary composite, surface treatment and secondary composite; The hexagonal boron nitride pretreatment step comprises spraying a pretreatment liquid into the hexagonal boron nitride, carrying out a heat preservation reaction, and after the reaction is completed, cooling, filtering, washing, and drying to obtain the pretreated hexagonal boron nitride; The pretreatment solution is a mixture of ethanol solution, vinylethoxydimethylsilane and polyvinylpyrrolidone; The primary composite step comprises placing the pretreated hexagonal boron nitride in an ethanol solution and dispersing it uniformly to obtain a pretreated hexagonal boron nitride mixed solution; adding benzoyl peroxide to styrene and dispersing it uniformly to obtain a monomer mixed solution; adding the monomer mixed solution dropwise to the pretreated hexagonal boron nitride mixed solution, controlling the addition rate to be 2.6-3.4 mL / min, adding polyvinyl alcohol after the addition is completed, stirring uniformly, heating in an oil bath, controlling the heating rate to be 1.6-2.2° C. / min, raising the temperature to 71-75° C., and keeping the temperature for reaction for 1.8-2.2 hours, and after the end of the heat preservation reaction, heating to 78-82° C. at a rate of 0.4-0.6° C. / min, and keeping the temperature for reaction for 6.0-8.0 hours, and after the end of the reaction, cooling and washing, and drying at 58-62° C. for 11.0-13.0 hours to obtain a primary composite microsphere; The surface treatment step is to place the primary composite microspheres in a sulfuric acid solution, mix them evenly, control the temperature to 38-42° C., keep the temperature and stir for 3.7-4.2 hours, then add an ethanol solution, cool them naturally to room temperature, wash and dry them, and obtain the sulfonated primary composite microspheres; The secondary composite step is to add the sulfonated primary composite microspheres to deionized water, then add octadecyltrimethylammonium chloride and didodecyldimethylammonium bromide, stir evenly, add modified graphene, stir at 495-510rpm for 1.4-1.6h, filter and wash after stirring, freeze-dry, and wait for it to naturally return to room temperature to obtain a multifunctional composite; The preparation method of the modified graphene comprises the following steps: placing the graphene in a hydrogen peroxide solution and a nitric acid solution, raising the temperature to 70-74°C, stirring and reacting for 5.8-6.2 hours, cooling and washing after the stirring and reaction is completed to obtain hydroxylated graphene; placing the hydroxylated graphene in N,N-dimethylformamide, adding sodium dodecylbenzenesulfonate, performing ultrasonic dispersion treatment, then adding oleic acid, stirring evenly, then adding dicyclohexylcarbodiimide and 4-dimethylaminopyridine, raising the temperature to 74-77°C, stirring and reacting for 9.8-10.4 hours, filtering, washing and drying after the reaction is completed to obtain the modified graphene.

2. A nitrile rubber composition according to claim 1, characterized in that The hexagonal boron nitride pretreatment step comprises spraying a pretreatment liquid into the hexagonal boron nitride, controlling the spraying rate to be 4.7-5.2 g / min, raising the temperature to 68-72° C. after the spraying, and keeping the temperature to react for 5.8-6.2 hours, and cooling, filtering, washing, and drying after the reaction to obtain the pretreated hexagonal boron nitride; The particle size of the hexagonal boron nitride is 150-180nm; The mass ratio of hexagonal boron nitride to pretreatment liquid is 9.8-10.2:98-105; In the pretreatment solution, the mass ratio of the ethanol solution, vinylethoxydimethylsilane and polyvinylpyrrolidone is 72-77:1.1-1.3:0.8-1.2; The mass concentration of the ethanol solution is 40-44%.

3. A nitrile rubber composition according to claim 1, characterized in that, In the first compounding step, the mass concentration of the ethanol solution is 78-82%; The mass ratio of the pretreated hexagonal boron nitride to the ethanol solution is 7.8-8.2:48-52; The mass ratio of the benzoyl peroxide to styrene is 0.11-0.13:18-23; The mass ratio of the pretreated hexagonal boron nitride mixed solution, the monomer mixed solution and the polyvinyl alcohol is 12.2-12.5:9.8-10.2:0.37-0.

43.

4. A nitrile rubber composition according to claim 1, characterized in that, In the surface treatment step, the mass concentration of the sulfuric acid solution is 93-98%; The volume concentration of the ethanol solution is 46-53%; The mass ratio of the primary composite microspheres, the sulfuric acid solution and the ethanol solution is 1.6-1.8 g: 47-53 mL: 38-43 mL.

5. A nitrile rubber composition according to claim 1, characterized in that, In the secondary compounding step, the freeze drying has a drying temperature of -34 to -30°C and a drying time of 9.7 to 10.2 hours; The volume mass ratio of the deionized water, the sulfonated primary composite microspheres, octadecyltrimethylammonium chloride, didodecyldimethylammonium bromide, and the modified graphene is 290-310 mL: 8.6-8.8 g: 0.6-0.8 g: 0.3-0.6 g: 2.0-2.5 g.

6. A nitrile rubber composition according to claim 1, characterized in that, In the preparation method of the modified graphene, the particle size of the graphene is 270-290nm; The mass volume ratio of the graphene, hydrogen peroxide solution and nitric acid solution is 13.1-13.7 g:95-105 mL:98-102 mL; The mass concentration of the hydrogen peroxide solution is 32-35%, and the mass concentration of the nitric acid solution is 62-67%; The mass volume ratio of the hydroxylated graphene, N,N-dimethylformamide, sodium dodecylbenzenesulfonate, oleic acid, dicyclohexylcarbodiimide and 4-dimethylaminopyridine is 3.0-3.5 g: 295-305 mL: 1.1-1.4 g: 4.0-4.2 g: 7.3-7.8 g: 0.32-0.36 g.

7. A nitrile rubber composition according to claim 1, characterized in that, The preparation method of the modified calcium carbonate comprises the following steps: placing calcium carbonate in anhydrous ethanol, adding Tween 80 and di(acetylacetonato)titanate diisopropyl for ball milling, wherein the ball milling temperature is 27-33 min, the ball milling speed is 224-235 rpm, and the ball-to-material ratio is 3-5:

1. After the ball milling is completed, the temperature is increased to 40-45° C., and the temperature is kept for reaction for 1.8-2.2 hours. After the reaction is completed, the modified calcium carbonate is filtered, washed, and dried to obtain the modified calcium carbonate. The particle size of the calcium carbonate is 200-220 nm; The mass ratio of the calcium carbonate, anhydrous ethanol, Tween 80 and di(acetylacetonato) diisopropyl titanate is 10.6-11.0:98-104:0.8-1.2:1.1-1.

3.

8. Use of a nitrile rubber composition according to any one of claims 1 to 7 in a screw pump stator rubber material.

Citation Information

Patent Citations

  • Hydrogenated nitrile rubber composition, vulcanized rubber and preparation method and application thereof

    CN117903511A

  • Graphene-based wear-resistant stator rubber composite material and preparation method thereof

    CN110724321A

  • High-wear-resistance anti-impact composite rubber and preparation method thereof

    CN111690186A